Bandar Kajum Terminal Design With Hybrid Architectural Approach In the City of Tebing Tinggi - Lubis, Femmy A. S.; Eddy, Firman; Abdillah, Wahyu (Talenta Publisher, 2021)
Terminal is a public service, a place for up and down passengers, a place for transfers between public and a place for the arrival and departure of public transport. The terminal can drive the transportation system because it is an infrastructure that can increase the mobility of vehicles and users. At the Bandar Kajum terminal in the City of Tebing Tinggi, it is necessary to maximize the function of the terminal both in terms of facilities and building mass that is able to combine strength, usability and beauty so as to produce balance. To produce such a large building mass, hybrid architecture was chosen as an approach in designing the Bandar Kajum terminal because hybrid architecture is a combination of different planning and design elements in an environment. The research method used in this study is an approach with a descriptive method that aims to identify the application of a hybrid to the design which is carried out through eclectic stages, modifications and merging as a way to combine building programs, this allows the functions of one another to be interrelated. support and interact with each other in the same building mass and elevate the locality of the Bandar Kajum terminal. Â